Audit Financiar Journal in 2017 (Audit Financiar, 2017)

(untitled)
The importance of financial literacy has increased due to factors such as the development of new financial products, the complexity of instruments and financial markets, political changes, and economic factors. For this reason, considerable measures have been performed recently by people and organizations with scientific competencies such as the World Bank, in respect of introducing, evaluating, and improving the people’s financial literacy. Due to the importance of this concept, this research has been performed with the goal of evaluating the role of the financial literacy training in the participation ratio of small and medium-size enterprises in financial markets. The statistical population of this research is composed of small and medium-size companies activating in the industrial city of Rasht. For the data analysis, the Structural Equation Modelling was used, by the PLS method. The results show that the financial literacy training has a positive and significant impact on the financial literacy level, and also on the market participation.